2021
DOI: 10.1111/ijd.15753
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and mortality rates with different treatment approaches of Merkel cell carcinoma: a systematic review and meta‐analysis

Abstract: Background Comprehensive treatment recommendations for Merkel cell carcinoma are complex. We aimed to systematically review the published data on recurrence and mortality rates associated with various treatment approaches for Merkel cell carcinoma.Methods Search of MEDLINE, Embase, Web of Science, and Scopus from inception to August 2015. Studies were included that reported comparative survival and recurrence data for two or more treatment modalities. Two reviewers independently reviewed and abstracted recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…However, this may be due to selection bias given the small sample size and a wide variety of treatment approaches. Although there is also evidence that the effect of traditional chemotherapy on the immune system may in fact lower cause‐specific mortality, in the long run, we did not identify any significant differences in disease recurrence or disease‐specific mortality in patients who received systemic therapy 29,30 . We were unable to directly compare patients receiving traditional chemotherapy with those receiving immunotherapy due to cohort size and crossover between the two groups—of the 11 patients who received immunotherapy, four also received chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, this may be due to selection bias given the small sample size and a wide variety of treatment approaches. Although there is also evidence that the effect of traditional chemotherapy on the immune system may in fact lower cause‐specific mortality, in the long run, we did not identify any significant differences in disease recurrence or disease‐specific mortality in patients who received systemic therapy 29,30 . We were unable to directly compare patients receiving traditional chemotherapy with those receiving immunotherapy due to cohort size and crossover between the two groups—of the 11 patients who received immunotherapy, four also received chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…Although there is also evidence that the effect of traditional chemotherapy on the immune system may in fact lower cause-specific mortality, in the long run, we did not identify any significant differences in disease recurrence or diseasespecific mortality in patients who received systemic therapy. 29,30 We were unable to directly compare patients receiving traditional chemotherapy with those receiving immunotherapy due to cohort size and crossover between the two groups-of the 11 patients who received immunotherapy, four also received chemotherapy. Though the size of our adjuvant therapy treatment groups was small and direct statistical comparisons were not sufficiently powered, it does appear that both positive outcomes and negative outcomes were reported in each individual treatment group.…”
Section: Stage IV Disease At Presentationmentioning
confidence: 99%
“…There are no data to confirm the benefit of perioperative chemotherapy in patients with stage I-III MCC regarding OS [ 5 , 17 , 38 , 40 , 41 ]. A large meta-analysis of 52 trials showed similar recurrence rates for patients receiving chemo-radiotherapy or only radiotherapy in aperioperative setting [ 42 ]. Thus, chemotherapy is not routinely recommended but may be considered in some selected cases, such as marginally resectable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering high MCC radiosensitivity, patients who are not suitable for surgery or refuse surgery may be offered definitive radiotherapy or radiochemotherapy [ 2 ]. Recent meta-analysis confirmed the noninferiority of this approach [ 42 ]. In our study, five patients treated with curative intent received radiotherapy alone, and only one disease recurrence after treatment was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the rare occurrence of this disease, high-quality clinical studies are lacking and treatment recommendations for MCC are complex and varied. Treatment approaches include wide local excision, Mohs surgery, radiotherapy and immunotherapy, as well as different combinations of these treatments (1). For wide local excision, the optimal margin width for primary MCC remains to be fully determined.…”
Section: Introductionmentioning
confidence: 99%